Effectivity of Control Functional Inspectorat in Department National Education Sulawesi North Provincies. - Akerina, Gabriela; Posumah, Johhny; Tampongangoy, Deysi (Sam Ratulangi University, 2015)
ABSTRACT Education is one of Indonesia’s development strategy are directed to build Indonesia. Implementation of government policies in education programs require Monitoring, Evaluation and Supervison. Therefore with the Implementation of a quality establishment of government officials, then appointed Inspectorate, as Supervison agency development, which serves to oversee the performance of the government on development activities, staffing activities, and service to the community. The purpose of this study wanted to know how the Effectiveness of Functional Supervison Inspectorate on National Education Departements North Sulawesi. This study used qualitative methods. Study focused (1) the supervision process on the Character of Effectiveness is Productivity, Efficiency, Satisfaction, Flexibility, and Development. (2) Effec tive monitoring results, is the achievement of goal or program policies target that has been set. Source of data / informants interviewed as many as 13 people consisting of 1 people Head office, 1 Treasurer, 1 holders program, and 10 person staff, and process data collection using interview techniques. The results showed that: in general, that functional supervision conducted by the Inspectorate to the National Education Departments North Sulawesi, seen from the 5 character of effectiveness is good. The timeliness in carrying out the task, achieve its intended purpose. In accordance with purpose of supervision. Their competence and results of monitoring that is capable of providing a change. Recommendations advice to the National Education Departements of North Sulawesi, leaders more confirms duties and functions of each fields. In order to better, structured, thorought and more appreciative of time in carrying out the task. Keywords : Functional Supervison Inspectorate